Experimental apparatus and methodology to test and quantify thermal performance of micro and macro-encapsulated phase change materials in building envelope applications. (December 2020) - Wijesuriya, Sajith; Tabares-Velasco, Paulo Cesar
Highlights: A state-of-the-art apparatus is used to conduct experiments in full scale wall experiments simultaneously. Four walls panels are constructed and tested in full cycles of heating and cooling. One microencapsulated and two macroencapsulated PCMs are tested. Experimental data from the four panels are made available for validation purposes. Abstract: Thermal energy storage (TES) is used as a viable technology to shift peak electricity demand caused by the space cooling requirements in buildings. Passive TES is implemented in building envelope via micro and macroencapsulation methods. This study describes the use of a state-of-the-art laboratory to test different PCM inclusions in simplified building walls. A microencapsulated PCM and two macroencapsulated PCMs are tested in a controlled environment to gather data for validation purposes of PCM modelling algorithms in building energy modelling programs. Data indicates that the chamber environment and the heating and cooling system can conduct full-cycle tests of wall panels with PCM inclusions. This study also generates data from parallel tests on 4 wall panels which can be used in building energy modelling programs to validate the PCM modelling algorithms. The cyclic tests also capture the thermal effects of PCMs and complex PCM behaviors like sub-cooling in PCM hydrate-salts.